Firm life cycle, corporate risk-taking and investor sentiment - Habib, A.; Hasan, Mostafa (Routledge, 2015)
This study investigates the corporate risk-taking and the performance consequences at different stages of the firm life cycle. We find that risk-taking is higher in the introduction and decline stages of the life cycle, but lower in the growth and mature stages. We also find that risk-taking during introduction and decline stage (growth and maturity stage) affects future performance adversely (positively). We also document that managerial risk-taking propensities increase during periods of high investor sentiment and firms in different life cycle stages respond to sentiment differently. Collectively, these results suggest that the firm life cycle has explanatory power for corporate risk-taking behaviour.